The flagellar photoresponse in Volvox species (Volvocaceae, Chlorophyceae) - Solari, Cristian Alejandro (2011)
Steering their swimming direction toward the light is crucial for the viability of Volvox colonies, the larger members of the volvocine algae. While it is known that this phototactic steering is achieved by a difference in behavior of the flagella on the illuminated and shaded sides, conflicting reports suggest that this asymmetry arises either from a change in beating direction or a change in beating frequency. Here, we report direct observations of the flagellar behavior of various Volvox species with different phyletic origin in response to light intensity changes and thereby resolve this controversy: Volvox barberi W. Shaw from the section Volvox sensu Nozaki (2003) changes the direction of the flagellar beating plane, while species encompassed in the group Eudorina (Volvox carteri F. Stein, Volvox aureus Ehrenb., and Volvox tertius Art. Mey.) decrease the flagellar beating frequency, sometimes down to flagellar arrest.